Strengthening Unity: allusion as a discursive practice in President Zelenskyy’s war rhetoric - Nedainova, Iryna (Respectus Philologicus, 2025)
This research examines the use of allusion as a powerful linguistic tool employed by President of Ukraine Volodymyr Zelenskyy in his international war discourse. Faced with the urgent need to secure assistance and support from the world community throughout the first year of Russia’s large-scale invasion, Zelenskyy strategically references well-known cultural facts to create a specific mental image of Ukrainians as a nation that upholds humanistic values such as tolerance, equality, and justice. The study analyses five types of audiences targeted by the Ukrainian President in his appeals: national parliaments, collective political bodies, business forums, educational institutions, and cultural assemblies. The findings demonstrate that allusion in his discourse is a key discursive practice tailored to each audience’s specificity. In every instance, the identified allusions reveal their emotional, evaluative, and associative connotations. In President Zelenskyy’s speeches, allusions also function as tactical instruments that yield effective results in his communication with international audiences. The paper concludes that the use of allusion makes the President’s speeches emphatic and his audiences more receptive, showcasing a high pragmatic capacity to craft desired images within foreign linguistic and cultural contexts.